2019
DOI: 10.1177/0310057x19840264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the EasyWarm® self-heating blanket with the Cocoon forced-air warming blanket in preventing intraoperative hypothermia

Abstract: The importance of preventing hypothermia in the perioperative period cannot be overemphasised. The use of active warming devices is advocated and practised widely. The forced-air warming (FAW) blanket is currently a popular modality. The BARRIER V R EasyWarm V R (M€ olnlycke Healthcare, Belrose, Australia) self-heating blanket, which does not require a power unit, has been proposed as an easy-to-use alternative to the FAW blanket. We conducted a singlecentre, randomized controlled trial to compare the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Thermal redistribution may be responsible for the fast heat loss seen during Phase I in the first hour. Phase II (heat transfer from the warmer perimeter to the rest of the environment) is characterised by a gradual linear decrease that occurs over a period of 2-4 hours, during which thermal loss surpasses metabolic heat generation [ 39 – 41 ]. Phase III (thermal homeostasis) starts following 3 - 4 h, once CTs of 33 to 35 degrees Celsius cause peripheral vasoconstriction [ 42 , 43 ].…”
Section: Background Basic Sciencementioning
confidence: 99%
“…Thermal redistribution may be responsible for the fast heat loss seen during Phase I in the first hour. Phase II (heat transfer from the warmer perimeter to the rest of the environment) is characterised by a gradual linear decrease that occurs over a period of 2-4 hours, during which thermal loss surpasses metabolic heat generation [ 39 – 41 ]. Phase III (thermal homeostasis) starts following 3 - 4 h, once CTs of 33 to 35 degrees Celsius cause peripheral vasoconstriction [ 42 , 43 ].…”
Section: Background Basic Sciencementioning
confidence: 99%
“…Regarding, Thapa et al study, he compared the EasyWarm self-heating blanket with the cocoon forced-air warming device, where he showed that there was no statistically significant difference between the 2 groups concerning the postoperative temperature, as the mean core temperature at 1, 2, and 3 hours was similar between the groups. [ 26 ] It is noteworthy to mention that self-warming blankets may have an additional cost-effectiveness benefit, particularly in low and middle-income countries. Thereby, large-scale RCTs are encouraged to establish the cost-effectiveness of these warming techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Several studies have shown promising results regarding the utility of self-warming blankets and forced-air devices in patients with perioperative hypothermia. [24][25][26] However, there is a lack of evidence comparing the impact of these techniques. Therefore, this study aims to evaluate the efficacy of self-warming blankets compared to active warming by forced-air devices in terms of the incidence of perioperative hypothermia.…”
Section: Introductionmentioning
confidence: 99%
“…The superiority of the SW blanket over standard hospital clothing has been reported elsewhere 10 . However, other randomised controlled trials which have compared the peri‐operative use of the SW blanket with the FAW blanket under spinal anaesthesia (SA) or general anaesthesia (GA) have yielded conflicting results 11–13 …”
Section: Introductionmentioning
confidence: 95%
“…10 However, other randomised controlled trials which have compared the peri-operative use of the SW blanket with the FAW blanket under spinal anaesthesia (SA) or general anaesthesia (GA) have yielded conflicting results. [11][12][13] The aim of this trial was to investigate whether the SW blanket is non-inferior to the FAW blanket in maintaining normothermia in patients undergoing elective unilateral total knee arthroplasty (TKA).…”
Section: Introductionmentioning
confidence: 99%